Effect of inoculation with white-rot fungi and fungal consortium on the composting efficiency of municipal solid waste. (March 2017) - Voběrková, Stanislava; Vaverková, Magdalena D.; Burešová, Alena; Adamcová, Dana; Vršanská, Martina; Kynický, Jindřich; Brtnický, Martin; Adam, Vojtěch
Graphical abstract: Highlights: Addition of white-rot fungi to OFMSW influenced compost maturation. Effectiveness of waste degradation and compost maturation depends on type of fungi. Inoculation with T. versicolor and F. fomentarius led to the lowest phytotoxicity. Abstract: An investigation was carried out on the effect of inoculation methods on the compost of an organic fraction of municipal solid waste. Three types of white-rot fungi ( Phanerochaete chrysosporium, Trametes versicolor and Fomes fomentarius ), and a consortium of these fungi, were used. The study assessed their influence on microbial enzymatic activities and the quality of the finished compost. It was found that the addition of white-rot fungi to municipal solid waste (after 37 days of composting) could be a useful strategy for enhancing the properties of the final compost product. In comparison with the control sample (compost without inoculation), it accelerates degradation of solid waste as indicated by changes in C/N, electrical conductivity and pH. However, the effectiveness of waste degradation and compost maturation depends on the type of microorganism used for inoculation. The presence of inoculants, such as Trametes versicolor and Fomes fomentarius, led to a higher degrading ratio and a better degree of maturity. This resulted in an increase of enzymatic activities (especially dehydrogenase and protease) and a germination index in comparison with inoculation using Phanerochaete chrysosporium or a consortium of fungi.